Risk aware and ALERT protocol for mitigating routing attacks in Mobile Ad hoc Networks (International Journal of Engineering and Computer Science, 2013)
Mobile Ad Hoc Networks (MANET) has been highly vulnerable to attacks due to the dynamic nature of its network infrastructure. Among these attacks, the routing attacks getting more attention because it’s changing the whole topology itself and it causes more damages to MANET. The existing algorithm not provides the anonymity protection and finding the malicious node with degree of evidence from the expert knowledge and detects the important factors for each node. In proposed method the ALERT protocol is developed for overcome the existing problem. ALERT protocol is mainly providing a high anonymity protection with low cost. Using proposed protocol the network fields are dynamically partitions into zones and zones are randomly chosen from the nodes as intermediate relay nodes, which form a non-traceable by anonymous route. Particularly in every routing step, a data sender or forwarder division the network field in order to disconnected itself and the destination into two zones. In the last step, the data are broadcast to k nodes in the destination zone providing k-anonymity to the destination. ALERT is also flexible to timing attacks and intersection attacks. In addition, the experiments demonstrate the effectiveness of proposed approach with the consideration of several performance metrics.